Exploration of Human Resources in MSMEs in Surakarta from a Sociodemographic Perspective - Harmastuti, Primadia Putri; Utomo, Bangun Prajadi Cipto; Mohd, Idaya Husna Binti (LPPM Universitas Duta Bangsa Surakarta, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy by contributing to employment, job creation, and local economic growth. This study explores the socio-demographic characteristics of MSME owners in Surakarta, focusing on age, gender, education level, work experience, and employment status. Using a quantitative approach, data were collected from 200 MSME operators through structured questionnaires and analyzed using univariate analysis. The results indicate that MSME owners in Surakarta have a diverse profile across all socio-demographic factors, which influences managerial skills, innovation, and business sustainability. Owners with higher education, longer work experience, and full-time commitment tend to perform better. Understanding these characteristics is essential for designing effective policies, training programs, and support initiatives to strengthen MSMEs and enhance their competitiveness in local and regional markets